Fifteen-minute consultation: the child with systemic arterial hypertension. Issue 1 (29th July 2016) - Singh, Cheentan; Jones, Helen; Copeman, Helen; Sinha, Manish D
Abstract : Hypertension in children is a relatively uncommon condition but its prevalence is increasing with the rising rates of excess weight during childhood. It is important that hypertension is diagnosed early in children, particularly in those with symptoms, in those with secondary causes and in those with target organ damage. This article presents a systematic approach to the evaluation of a child with arterial hypertension, highlighting important points on history and examination, out-of-office monitoring and baseline investigations before consideration for more detailed investigations and treatment.